Pengaruh Kepribadian dan Kompetensi Karyawan Terhadap Prestasi Kerja Karyawan Divisi SDM PT. Pupuk Sriwidjaja Palembang (Persero) - Giska Amanda; Rismansyah Rismansyah; Reva Maria Valianti (Universitas PGRI Palembang, 2020)
ABSTRACTÂ The problem of this research is the lack of socialization among employees and the ability of employees to carry out tasks so that work performance does not increase. This study aims to determine